Severe Influenza in 33 US Hospitals, 2013–2014: Complications and Risk Factors for Death in 507 Patients. (30th July 2015) - Shah, Nirav S.; Greenberg, Jared A.; McNulty, Moira C.; Gregg, Kevin S.; Riddell, James; Mangino, Julie E.; Weber, Devin M.; Hebert, Courtney L.; Marzec, Natalie S.; Barron, Michelle A.; Chaparro-Rojas, Fredy; Restrepo, Alejandro; et al.
Abstract : BACKGROUND: Influenza A (H1N1) pdm09 became the predominant circulating strain in the United States during the 2013–2014 influenza season. Little is known about the epidemiology of severe influenza during this season. METHODS: A retrospective cohort study of severely ill patients with influenza infection in intensive care units in 33 US hospitals from September 1, 2013, through April 1, 2014, was conducted to determine risk factors for mortality present on intensive care unit admission and to describe patient characteristics, spectrum of disease, management, and outcomes. RESULTS: A total of 444 adults and 63 children were admitted to an intensive care unit in a study hospital; 93 adults (20.9%) and 4 children (6.3%) died. By logistic regression analysis, the following factors were significantly associated with mortality among adult patients: older age (>65 years, odds ratio, 3.1 [95% CI, 1.4–6.9], P =.006 and 50–64 years, 2.5 [1.3–4.9], P =.007; reference age 18–49 years), male sex (1.9 [1.1–3.3], P =.031), history of malignant tumor with chemotherapy administered within the prior 6 months (12.1 [3.9–37.0], P <.001), and a higher Sequential Organ Failure Assessment score (for each increase by 1 in score, 1.3 [1.2–1.4], P <.001). CONCLUSION: Risk factors for death among US patients with severe influenza during the 2013–2014 season, when influenza A (H1N1) pdm09 was the predominant circulating strain type, shifted in the first postpandemic season in which it predominated toward those of a more typical epidemic influenza season. Infect. Control Hosp. Epidemiol. 2015;36(11):1251–1260